Urinary 8-OHdG level is not affected by geography and trace elements in nail of residents of Addis Ababa: It is shaped by interactions between different social factors. (2022) - Dessie, Bitew K.; Mehari, Bewketu; Tefera, Molla; Osman, Mahlet; Tsegaye, Yosef; Gari, Sirak Robele; Desta, Adey F.; Melaku, Samuel; Alamirew, Tena; Goodson, Michaela L.; Walsh, Claire L.; Zeleke, Gete; et al.
Abstract: The objective of this study was to evaluate the association between exposure to heavy metals and oxidative DNA damage among residents living in the potentially more polluted downstream (Akaki-Kality) area of Addis Ababa, in comparison to the upstream area (Gullele). For this, 8-hydroxy-2′-deoxyguanosine (8-OHdG) was used as a biomarker for oxidative DNA damage and heavy metals (Fe, Zn, Mn, Cu, Ni, Cr, Pb, As) as indicators of exposure. The concentrations of heavy metals in nails were determined using inductively coupled plasma optical emission spectroscopy (ICP-OES), and 8-OHdG in urine using Enzyme-Linked with Immunosorbent Assay (ELISA), from 95 residents of the two areas, upstream and downstream. The urinary 8-OHdG concentration was not significantly different (p = 0.05) between the two Sub-Cities, with mean of 18.50 ± 4.37 ng/mg Creatinine in Akaki-Kality and 17.30 ± 5.83 ng/mg Creatinine in Gullele. Also, there were no statistically significant (p = 0.05) difference among the different demographic groups according to gender, age, educational status, body mass index or habit of alcohol consumption. However, the interactions of sex with age, sex with alcohol consumption and alcohol consumption with education were found to affect the urinary 8-OHdG levels of residents of the two Sub-Cities. The mean concentrations (µg/g) of the elements were 488 and 1035 for Fe, 106 and 251 for Zn, 13.0 and 31.2 for Mn, 5.23 and 6.63 for Cu, 11.2 and 7.39 for Ni, 2.23 and 2.02 for Cr, 0.09 and 0.63 for Pb; and 0.16 and 0.25 for As, in nail samples from Akaki-Kality and Gullele, respectively. The determined concentrations of the heavy metals in nails were not significantly associated (p = 0.05) with the corresponding urinary levels of 8-OHdG. Hence, the observed 8-OHdG might have been caused by environmental exposure to toxic substances other than the analyzed heavy metals. Graphical Abstract: ga1 Highlights: 8-OHdG was measured in urine using ELISA. Kruskal-Wallis, PCA, Box plot and correlation analysis techniques were applied. ICP-OES was used for detection of trace elements in nail samples. No significant association was observed between 8-OHdG and trace elements. Urinary 8-OHdG was shaped by interactions between different social factors.